Self-Triggered Consensus of Vehicle Platoon System With Time-Varying Topology - Wang, Weiping; Wang, Chunyang; Guo, Yongzhen; Luo, Xiong; Gao, Yang (Frontiers in Neurorobotics, 2020)
This paper focuses on the consensus problem of vehicle platoon system with time-varying topology via self-triggered control. Different from traditional control methods, a more secure event-triggered controller considering the safe distance is designed for vehicle platoon system. Then, a Lyapunov function was designed to prove the stability of the platoon system. Furthermore, based on the new event-triggered function, a more efficient and energy efficient self-triggered control strategy is designed by using Taylor formula. The new self-triggered control strategy can directly calculate the next trigger according to the state information of the last trigger. It avoids continuous calculation and measurement of vehicles. Finally, the effectiveness of the proposed two self-triggered control strategies are verified by numerical simulation experiments.